Behaviour of hybrid fibers in reinforced recycled concrete aggregate beam (50% of recycled aggregate) - Ahmad Syazwan, Saiddin (2017)
Green building material can reduce the pollution and promotes conservation of reducing non-renewable resources. Recycled concrete aggregate is a waste concrete material that have been crushed and then recycled to be used as green construction material. Concrete mixture that use recycled concrete aggregate usually have low in strength compared to normal concrete mixture. By adding kenaf and steel fiber (hybrid) into the mixture, it may have potential to improve reinforced the properties of cement and also overcome the weakness of reinforced recycled concrete aggregate. Four beams are constructed in this study, which is standard control beam and another three beams with 50 % of recycled concrete aggregates replaced coarse aggregates added with (0%,1% and 2%) volume of hybrid fibers. Hybrid fibers reinforced recycled concrete aggregate beams had potential to become more ductile compared to normal concrete beam.